(untitled) (Journal of Nepal Geological Society, 2000)
There are about 79 dams in Pakistan, which meet the ICOLD criteria of ’large dams’. This paper deals with certain engineering geological problems of dam construction that are peculiar to Pakistan. These include difficult foundations, reactive aggregates, deep alluvial filled valleys, and seismically unstable areas. In addition, associated problems including very high floods and phenomenal sedimentation are also discussed. Owing to the complex geotectonic setting, various critical problems or engineering geological nature occurred during the construction of such large dams as the Mangla and Tarbela in northern Pakistan. Some of these problems were beyond the boundaries of experience. Appropriate solutions, which sometimes required untried techniques, were devised and successfully implemented. The paper also discusses special foundation treatment provided in the design of a proposed large dam.